Digital Transformation in Primary Healthcare Services: An Analysis of Telemedicine Effectiveness on Access and Quality of Public Health Services - Yuni Vivi Santri P; Susi Amenta Beru Perangin-angin; Nona Try Agista (PT. Anagata Sembagi Education, 2026)
Digital transformation has fundamentally reshaped the delivery of primary healthcare services globally, with telemedicine emerging as a pivotal mechanism for expanding access and improving service quality. The COVID-19 pandemic served as a critical inflection point, accelerating telemedicine adoption across diverse healthcare systems. Objective: This study aims to analyze the effectiveness of telemedicine in enhancing access to and quality of primary healthcare services through a systematic review of existing literature. Methods: A comprehensive literature review was conducted using peer-reviewed articles published between 2021 and 2025. A total of 40 studies were identified and analyzed across dimensions of healthcare access, service quality, patient satisfaction, clinical outcomes, and implementation barriers. Results: Telemedicine significantly improved geographic access to care, particularly in rural and underserved communities. Clinical quality indicators were largely comparable to in-person care, with notable benefits in chronic disease management, follow-up care, and patient engagement. However, disparities persisted among elderly populations, low-income groups, and regions with limited digital infrastructure. Conclusion: Telemedicine represents an effective and scalable approach to primary healthcare transformation, though its equitable implementation requires targeted policy interventions addressing digital literacy, infrastructure, and regulatory frameworks